2015
DOI: 10.1186/s13063-015-0762-6
|View full text |Cite
|
Sign up to set email alerts
|

The Beyond Ageing Project Phase 2 - a double-blind, selective prevention, randomised, placebo-controlled trial of omega-3 fatty acids and sertraline in an older age cohort at risk for depression: study protocol for a randomized controlled trial

Abstract: BackgroundLate-life depression is associated with high rates of morbidity, premature mortality, disability, functional decline, caregiver burden and increased health care costs. While clinical and public health approaches are focused on prevention or early intervention strategies, the ideal method of intervention remains unclear. No study has set out to evaluate the role of neurobiological agents in preventing depressive symptoms in older populations at risk of depression.Methods/DesignSubjects with previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Omega-3 a highly unsaturated fatty acid (HUFAs), number of studies was concerned with the addition of Omega-3 to the treatment regimen of already depressed patients. Which have been shown it to have beneficial effect to alleviate depressive symptoms in patients already receiving antidepressant treatment [35,83,85]. However, the evidence is not conclusive as the results of different studies are not univocal.…”
Section: Content Of the Intervention Programsmentioning
confidence: 57%
See 1 more Smart Citation
“…Omega-3 a highly unsaturated fatty acid (HUFAs), number of studies was concerned with the addition of Omega-3 to the treatment regimen of already depressed patients. Which have been shown it to have beneficial effect to alleviate depressive symptoms in patients already receiving antidepressant treatment [35,83,85]. However, the evidence is not conclusive as the results of different studies are not univocal.…”
Section: Content Of the Intervention Programsmentioning
confidence: 57%
“…There are many studies which has proven that this approach is effective, feasible and acceptable to people [17,50,82]. Other studies are still in progress [83].…”
Section: Community-based Prevention Programmentioning
confidence: 99%
“…Neuroimaging studies are also being used to help to evaluate the neurobiological effects of omega-3 in mental health. For example, a current RCT is assessing the effect of LCn3 treatment in an older age cohort on depressive symptoms and correlating these with brain changes [123].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Depressive illness in the elderly increases morbidity, disability, functional decline, caregiver burden and premature mortality, and enhances health care costs [ 2 , 6 , 9 ]. LLD represents the major risk factor for suicide in the elderly [ 10 ].…”
Section: Depression In Agingmentioning
confidence: 99%
“…Interestingly, there is a direct link between reduction in hippocampal size and impaired mnesic functions in aged depressed patients [ 31 ]. Neuroimaging studies have demonstrated that LLD is associated with reduced gray matter volume in frontostriatal and limbic networks (including prefrontal cortex, hippocampus, amygdala, putamen, and thalamus) [ 9 , 32 ].…”
Section: Depression In Agingmentioning
confidence: 99%